ANALISIS KONSERVASI KEARIFAN LOKAL LUBUK LARANGAN DESA BARU PUSAT JALO - Wulandari, Titis; Kurniadi, Muhammad Dwi; Aldino, .; Arsih, Fitri; Lufri, . (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2023)
This article describes environmental conservation based on local wisdom in Desa Baru Pusat Jalo from the perspective of religion, management and science. Based on interviews and observations. This study uses a qualitative approach with a case study design with a focus on local wisdom in Lubuk Ban, including adherence to customary law. This article shows that the new central church has local wisdom in Lubuk Ban. Lubukban was established based on a Village Protection Agreement, which was later confirmed in Village Regulations and Government Decrees. The existence of Lubuk Ban in the new village center of Jalo aims to improve the community's economy, protect the river and fish ecosystems that flow into the river. The governance of the existence of Lubuk Ban is contained in customary rules and is also based on Islamic religious teachings. If the community violates it, it will be subject to applicable law. Environmental conservation in the new village center of Jalo is an effort by the local community to protect nature from environmental damage.